2017
DOI: 10.3892/etm.2017.4648
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-503 suppresses cell proliferation and invasion in osteosarcoma via targeting insulin-like growth factor 1 receptor

Abstract: MicroRNAs (miRs) are a class of small non-coding RNAs and have key roles in various cancer types. Recently, miR-503 has been reported to act as a tumor suppressor in osteosarcoma. However, the detailed mechanism of the regulatory role of miR-503 in osteosarcoma cell proliferation and invasion has largely remained elusive. The present study found that miR-503 was significantly downregulated in osteosarcoma tissues compared to that in matched adjacent non-tumorous tissues. In addition, the expression of miR-503 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…We also explored the mechanisms underlining the anti‐tumor effects after targeting mutant TP53. The IGF‐1R signaling pathway plays a significant role in tumor proliferation, growth, and migration in osteosarcomas . Down regulation of IGF‐1R may be one aspect of the mechanism underlining the inhibition of proliferation, colony formation, and migration arising after targeting mutant TP53 in this study.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…We also explored the mechanisms underlining the anti‐tumor effects after targeting mutant TP53. The IGF‐1R signaling pathway plays a significant role in tumor proliferation, growth, and migration in osteosarcomas . Down regulation of IGF‐1R may be one aspect of the mechanism underlining the inhibition of proliferation, colony formation, and migration arising after targeting mutant TP53 in this study.…”
Section: Discussionmentioning
confidence: 74%
“…The IGF-1R signaling pathway plays a significant role in tumor proliferation, growth, and migration in osteosarcomas. 25,[35][36][37] Down regulation of IGF-1R may be one aspect of the mechanism underlining the inhibition of proliferation, colony formation, and migration arising after targeting mutant TP53 in this study. Indeed, it has been reported that down regulation of IGF-1R expression is associated with decreased proliferative activity in osteosarcoma cells.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…MicroRNAs (miRNAs) have great potential to be useful biomarkers in cancer research. 14 miR-32 functioned as an antitumor miRNA, which has been shown to be downexpressed and to suppress some target genes to inhibit the malignant processes of lung cancer. [11][12][13] It is also common knowledge that abnormal miRNAs expression plays important regulatory roles in the occurrence and development of multiple cancers in which they maybe conduct as tumor suppressors or oncogenes by adjusting cell differentiation, proliferation, cell cycle, apoptosis, or metastasis.…”
mentioning
confidence: 99%